Hepatitis E Virus An Emerging Zoonotic and Foodborne Pathogen - Ruggeri, Franco Maria. (SpringerBriefs in Food, Health, and Nutrition,, 2013)
Hepatitis E (HEV) is a viral infectious disease that infects humans and domestic, wild, and synanthropic animals alike. In developing countries, the disease often presents as an epidemic, transmitted primarily through the fecal-oral route. In recent years, sporadic cases have also been documented in industrial countries, including Europe. The identification and characterization of animal strains of HEV from pigs, wild boar, and deer, and the demonstrated ability of cross-species infection by these animal strains raise potential public health concerns for foodborne and zoonotic transmission of the virus. This Brief will provide a thorough overview of HEV. It will discuss the epidemiology and pathogenesis of the virus in both humans and animals, review detection methods, and provide methods for its control and prevention.